The Role of 4D Flow MRI-derived Wall Shear Stress in Aortic Disease: A Comprehensive Review - Ying Liu; Xiaolin Mu; Yixin Wang; Zhe Xu; Yang Song (Reviews in Cardiovascular Medicine)
Aortic diseases, such as aortic dissection and aortic rupture, often lead to catastrophic complications, significantly increasing morbidity and mortality. Population-based screening for early detection in asymptomatic individuals is not feasible due to high costs and practical challenges. However, recent advancements in four dimensions (4D) Flow magnetic resonance imaging (MRI) offer a comprehensive tool for evaluating hemodynamic changes within the aortic lumen. This technology allows for the quantification and visualization of flow patterns and the calculation of advanced hemodynamic parameters, such as wall shear stress (WSS). WSS is crucial in the development, risk stratification, and surgical outcomes of aortic diseases and their complications, enabling noninvasive and quantitative screening of high-risk populations. This review explores the current status and limitations of 4D flow MRI-derived WSS imaging for aortic disease.